2011
DOI: 10.4314/sajas.v41i1.66041
|View full text |Cite
|
Sign up to set email alerts
|

Parameter estimates for reproductive output and product quality traits of ostrich females within breeding seasons

Abstract: Data involving monthly records of egg production (EP), chick production (CP), hatchability (H), mean egg weight (MEW) and mean day-old chick weight (MCW) were analysed using REML procedures. All traits were treated as hen traits. Egg production of young birds increased to reach a peak of approximately 4 to 5 eggs per month relatively late in the breeding season (September to December). Older hens reached a higher peak of 6 to 9 eggs per month earlier in the breeding season (August to September). There was a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Most nutritional studies in ratites have been conducted in ostriches (reviewed by Angel, 1996;Ullrey and Allen, 1996;Aganga et al, 2003;Cooper et al, 2005), because it was the first and is currently the most commonly farmed ratite species (Gillespie and Schupp, 1998;Cloete et al, 2004;Ipek and Sahan, 2004;Lambrechts, 2004;Fair et al, 2005;Cloete et al, 2006). Thereafter, when rhea farming started to grow as an agricultural venture, the need for information about nutrient requirements was met by direct extrapolation from that available for ostriches (Angel, 1996;Carbajo Garcia et al, 1997;Aganga et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Most nutritional studies in ratites have been conducted in ostriches (reviewed by Angel, 1996;Ullrey and Allen, 1996;Aganga et al, 2003;Cooper et al, 2005), because it was the first and is currently the most commonly farmed ratite species (Gillespie and Schupp, 1998;Cloete et al, 2004;Ipek and Sahan, 2004;Lambrechts, 2004;Fair et al, 2005;Cloete et al, 2006). Thereafter, when rhea farming started to grow as an agricultural venture, the need for information about nutrient requirements was met by direct extrapolation from that available for ostriches (Angel, 1996;Carbajo Garcia et al, 1997;Aganga et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Female ostriches during the first season started laying eggs late by one month compared to elder breeders, thereby produced less eggs. Fair et al (2005) showed that 2-year old hens (just mature) started slowly, increased egg production steadily up to five months into the breeding season but produced least eggs. This was attributed to the lack of sexual maturity and experience.…”
Section: Discussionmentioning
confidence: 99%